2019
DOI: 10.3390/biom10010024
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Cefuroxime Axetil/Cyclodextrin System with Enhanced Solubility and Antimicrobial Activity

Abstract: This study aimed to investigate changes in the solubility and antimicrobial efficacy of cefuroxime axetil (CA) when incorporated into cyclodextrin (CD). While choosing the CD, the validated in silico model was used. A theoretical model based on docking and molecular mechanics/generalized born surface area was validated using a curated dataset of API (active pharmaceutical ingredient)–CD stability constants. The library of commonly used cyclodextrins was virtually screened, indicating CA –hydroxypropyl-βCD (HPβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The increase in pharmacological activity for API with a different mechanism of action after their introduction into CD cavities, confirmed by the results of in vivo studies were reported, eg, for antimicrobial activity cefuroxime axetil, for the anti-inflammatory activity of naringenin and for reduction of arterial pressure by valsartan. [50][51][52] In our previous studies, we also confirmed that an increase in the analgesic effect for sumatriptan after introduction into CD structures was possible. 23 Other studies confirming the beneficial impact of CD systems on the analgesic effect were also obtained in the case of ketoprofen, where antipyretic, analgesic and anti-inflammatory effects increased, and in the mice study for meloxicam, where the elevated API serum levels maximized its analgesic activity.…”
supporting
confidence: 85%
“…The increase in pharmacological activity for API with a different mechanism of action after their introduction into CD cavities, confirmed by the results of in vivo studies were reported, eg, for antimicrobial activity cefuroxime axetil, for the anti-inflammatory activity of naringenin and for reduction of arterial pressure by valsartan. [50][51][52] In our previous studies, we also confirmed that an increase in the analgesic effect for sumatriptan after introduction into CD structures was possible. 23 Other studies confirming the beneficial impact of CD systems on the analgesic effect were also obtained in the case of ketoprofen, where antipyretic, analgesic and anti-inflammatory effects increased, and in the mice study for meloxicam, where the elevated API serum levels maximized its analgesic activity.…”
supporting
confidence: 85%
“…Antimicrobial activity for curcumin and piperine in free forms was previously confirmed 59,60 . Also, 2-hydroxypropyl-b-cyclodextrin showed some antibacterial effect 61 , but more importantly, it increases bactericidal effect of other substances 62,63 . Cyclodextrins, according to many mechanisms, can counteract infections by decreasing antibiotic resistance via complexation 64 , lowering the cell-to-cell (quorum sensing) communication 65 , and blocking poreforming toxins 66 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, meropenem/β-cyclodextrin showed significant changes in MIC values (4.0 mg/mL) against P. aeruginosa compared to meropenem (8.0 mg/mL), what can indicate changes in the permeability of the outer membrane [ 20 ]. Also, significant improvement in water solubility was observed in case of tebipenem pivoxil, where statistically significant increases in dissolution rate were observed in the case of the tebipenem pivoxil/β-cyclodextrin complex [ 21 ], cefuroxime axetil, where after 2 min the cefuroxime axetil/hydroxypropyl-β-cyclodextrin inclusion sample was dissolved in 63%, while pure cefuroxime axetil was only dissolved in 21% [ 22 ], or cetirizine/β-CD for taste-masking purpose [ 23 ]. The use of cyclodextrin-based systems, in addition to affecting the dissolution rate of biomolecules, may also affect the prolonged and/or delayed release of the active from system [ 24 ].…”
Section: Introductionmentioning
confidence: 99%